BAQSÍSHÍLÍQ MEKTEPLERINÍŃ KÓRKEM ATQARÍWSHÍLÍQ ÓNERI - Erejepov, A.A. (SCIENCE and SOCIETY, 2023)
The article tells about the national art schools Bakshilik. In the performing repertoire of the art of bakhshi, the skill of performing love epics "Garip Ashyk", "Gurugly", "Yusuf Ahmet", "Ashik Najep", "Kyrmandali", "Bazergen" is popular among the people. The role of national art schools in the development of folk art, ways and programs for the preservation and development of national values were also widely covered.